The Effect of Incentives on Employee Turnover in the Service - Mohammed Ahmed Al-Suhaymi (Journal of Arts, Literature, Humanities and Social Sciences, 2025)
This study investigates the impact of incentive systems on employee turnover in the service sector, which relies heavily on human resources to provide high-quality services and ensure customer satisfaction. Drawing on a quantitative research design, a structured questionnaire was administered to employees in different service-oriented organizations, including hospitality, retail, and healthcare. The data revealed that both financial incentives (e.g., salary increments, bonuses) and non-financial incentives (e.g., recognition, training, flexible scheduling) significantly influence job satisfaction and organizational commitment, ultimately reducing turnover intentions. Interestingly, the results suggest that non-financial incentives can exert a greater long-term impact by fostering intrinsic motivation, while financial incentives often address immediate economic needs. A multiple regression analysis demonstrated that incentive systems explain a substantial portion of the variance in turnover intentions, indicating theirvital rolein maintainingastableworkforce. Thestudyconcludes that organizations should adopt a holistic and balanced incentive strategyto enhance employee retention, combiningboth monetary and non-monetary rewards. Moreover, management should cultivate a supportive culture that emphasizes professional development and acknowledges individual contributions. Future research is recommended to include cross-sectional and longitudinal comparisons across various service sectors to provide broader insights into how incentives can be optimized for different organizational contexts.